Design,Analysis And Manufacturingof Garbage compactor-a Review - Surajgavali(Student); Dr.R.J.Patil(Principal) (International Journal of Innovations in Engineering Research and Technology, 2021)
The collection of waste is vital work that ensures our communities remain pleasant environments in which to live. But major problem we are facing today is transportation of the waste which can be reduced by compacting or reducing size of particular waste. A compactor canbe used to reduce the volume of waste streams. The waste weight will remain the same so there will be no savings from the total amount of waste produced. However, savings will occur because waste volume will be reduced by approximately 80% which will decrease the number of times the dumpster will need to be emptied, therefore resulting in lower pick up fees.